Hubungan Stres Kerja dengan Kinerja Bidan dalam Masa Pandemik Covid-19 di Kota Pontianak - Affi Zakiyya; Monika Natalia Pratiwi; Dianna Dianna (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
ABSTRACTÂ Work stress on midwives during the COVID-19 pandemic can occurred due to high working hours, long working hours, mindset, limited number of health workers while the number of patients continued to grow and work safety procedures continue to change along with the development of the virus. If midwives did not manage work stress properly this will have an impact on their performance in providing health services to patients. To analyse the relationship between work stress and the midwife performance during pandemic covid-19 in Pontianak. Quantitative with cross sectional design. The sample of this study was 43 midwives in Pontianak. Sampling with total sampling method. The results of this study were 23 respondents (53.5%) who experienced work stress and 20 respondents (46.5%) who did not experience work stress. On the performance of midwives there were 25 respondents (58.1%) with good performance and 18 respondents (41.9%) with poor performance. Based on the Chi-square test, the p value = 0.004 meant that the sig value was smaller than(0.004 <0.05) indicating that work stress was related to the performance of midwives during the COVID-19 pandemic in Pontianak. Work stress was related to the performance of midwives during the COVID-19 pandemic in Pontianak with a p value = 0.004. Keywords: Work Stress, Midwife Performance, COVID-19 Pandemic